Pengembangan Motif Cap untuk Keterampilan Membatik Bagi Perempuan Warga Desa Jatirejoyoso, Kepanjen Malang Jawa Timur - Robby Hidajat; Pujiyanto Pujiyanto; Ike Ratnawati; Muhammad Afaf Hasyimy; Allfa Andranica Devya A; Gesang Bayu Pamungkas (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
Jatirejoyoso Village, Kepanjen District, Malang Regency is an agricultural village that still depends on selling agricultural products for its livelihood. Some other people work as factory, workshop and trader workers. As for women, after high school many get married and become housewives. Environmental analysis, Jatirejoyoso Village has potential that is very close to the development of the Malang Mask Wayag performance art. Typical performance art performed by masked dancers, presenting the story of Panji. The Research Team combined two conditions that can complement each other, namely that women who become housewives are able to develop skills without having to leave the house, namely developing stamped motifs from cardboard with wayang mask ornament patterns. This is an opportunity to make simple and cheap batik crafts. The method uses design, training and mentoring. The activity stages are carried out starting from subject analysis, development, ornament design, training, and evaluation of results. Indicators of the success of this activity are the enthusiastic involvement of participants, understanding of batik stamp design skills, and the process of stamping and coloring.